Desempenho e emissões de motor gerador operando com blendas de diesel/óleo de soja, diesel/óleo de linhaça e diesel/óleo de crambe - Leite, Danilo (2018)
In Brazil, rural communities away from the big centers, away from transmission and distribution electric grid, doesn´t have electric power hindering local economic progress. So, an alternative to a solution of the problem is a source of energy through fuels a base of vegetable oil, local raw material, renewable and of less environmental impact, justifying this work. The production service and the performance and emissions of a diesel generator set operating with fuels a vegetable oil base of soybean, linseed and crambe. The fuels were tested from a 5kVA generator set, without mechanical adaptation and connected to a electrical charges bank manufactured to dissipate the generated electric energy. Biofuels were obtained from the mixture of conventional diesel oil with soybean oil, linseed and crambe at incremental levels of 10%, 30%, 50% and 70% of vegetable oil in the composition of the fuel mixture and submitted to physicochemical viscosity analysis and density. In the evaluation of the performance of the generator was measured voltage (V), electric current (A), frequency of electric current (Hz), electrical power (W), wight (g), generator set noise (dB) and measured the exhaust gas concentration. The results of the studies show us that mixtures of conventional diesel (B8) with vegetable oil of soybean, linseed and crambe, in concentrations of up to 30%, presented with an effective technical alternative for a partial replacement of conventional diesel in the production of electric power, with reduction in emission levels and maintenance of the performance of the generator set.